Fatigue failure mechanism of aluminium alloy riveted single-shear lap joints. (April 2023) - Wang, He; Li, Hechang; Zhao, Yue; Liu, Xuetong; Peng, Jinfang; He, Liping; Liu, Jianhua; Zhu, Minhao
Highlights: The fatigue test of single shear lap joints riveted by swage-locking pins was carried out. The damage evolution process and fatigue fracture behavior of contact interface were studied. The surface-surface fretting wear of the lap plates is not uniform, resulting in two kinds of fringe morphology of the contact interface: wear and non-wear areas. An image recognition algorithm is used to extract and calculate the area of the debris area. The fatigue failure mode of joint is related to load. The lap plate fatigue fracture under low load, and the rivet shear fracture under high load. Under the influence of the contact stress, the micro-crack propagates along the direction of 75 degrees from the contact surface at the initial stage of crack propagation. Abstract: The fatigue life of the joint, the evolution process of the contact interface damage and the fatigue fracture behaviour of the joint were studied through a fatigue test of an aluminium alloy single-shear lap joint riveted by a swage-locking pin. Combined with optical microscope (OM), scanning electron microscope (SEM), electron probe microanalyzer (EPMA) and three-dimensional white light interferometry (WLI) and other equipment, and using computer image recognition algorithm, the characteristics and area of debris at the interface of the lap-plate under different cycles were studied, and the damage evolution process of the contact area was revealed. Results show two fatigue failure modes of the joint under different fatigue loads. The contact at the interface is non-uniform, and two morphologies are observed in the contact area: wear and non-wear areas. As the cycles increased from 130, 000 to 230, 000, the debris area in the contact area increased by 22%, while that in the non-contact area increased by 152%. Micro-cracks are generated in the contact area under the action of fretting wear, and the highest maximum principal stress exists at the crack source.